A Latent Resilience Capacity: Individual and Organizational Factors Associated with Public Library Managers' Willingness to Engage in Post‐Disaster Response and Recovery. Issue 4 (9th June 2019) - Linder, Michal
Abstract : Recent natural disasters in the United States have prompted numerous local and voluntary organizations to set aside routine activities and assume crisis‐related roles to meet the needs of the community. Despite such efforts, emergency authorities seldom utilize their capacity effectively. With the shift toward a more collaborative approach to emergency management, scholars and government officials call for identifying existing and potential actors in the preparedness phase. Efforts to anticipate potential decisions and actions of organizations that do not routinely deal with disasters, however, necessitate a better understanding of how managers view their post‐disaster‐related roles and what may account for such perceptions. Focusing on public libraries, I drew on information gathered through surveys and interviews with library officials and found that perceptions and projected behavior vary across libraries. To further investigate variations in willingness to engage in response and illuminate the driving forces behind such projected behavior, I explored context‐related characteristics in which library officials operate as well as factors related to individual managerial practices. Specifically, how managers define themselves in their public service role and the perceptions they hold of their organizations. 潜在弹性能力：与灾后响应和恢复工作中公共图书管理员参与意愿相关的个人因素和组织因素: 近期美国自然灾害事件已推动诸多地方组织和志愿组织将日常活动放在一边，转而在灾害危机中担当起满足社区需求的角色。尽管做出了此番努力，应急部门却很少有效地发挥其能力。为顺应一种更具合作性的应急管理方法，学者和政府官员呼吁识别出灾害预备阶段中的现有行为者和潜在行为者。（如果）期待机构作出与往常应对灾害所不同的决定和行为，则必须更深入地理解管理者如何看待其灾后应发挥的作用，以及造成这样看法的原因可能是什么。笔者聚焦于公共图书馆，选取与图书馆馆员进行面谈和调查后收集的信息，发现不同图书馆之间的看法和行为存在差异。为进一步调查灾害响应参与意愿的差异，并阐明这类行为背后的驱动因素，笔者探索了与灾害背景相关的、图书馆馆员采取行动的特征，以及与个人管理实践相关的因素。特别地，（笔者探索了）管理者如何定义其在公共服务中扮演的角色，和如何看待其所属组织。 Una capacidad de resiliencia latente: factores individuales y organizacionales asociados a la voluntad de los gerentes de bibliotecas públicas de involucrarse en la respuesta y en la recuperación después de los desastres: Los recientes desastres naturales en los Estados Unidos han llevado a numerosas organizaciones de voluntariado locales a dejar de lado las actividades de rutina y asumir roles relacionados con las crisis para satisfacer las necesidades de la comunidad. A pesar de estos esfuerzos, las autoridades de emergencia no utilizan a menudo sus capacidades efectivamente. Con el cambio hacia un método más colaborativo de gestión de emergencias, los académicos y los oficiales de gobierno piden identificar actores existentes y potenciales en la fase de preparación. Sin embargo, los esfuerzos para anticipar las decisiones y acciones potenciales de las organizaciones que no se ocupan habitualmente de los desastres requieren una mejor comprensión de cómo los gerentes ven sus roles relacionados con el desastre y lo que puede explicar esas percepciones. Centrándome en las bibliotecas públicas, obtuve información recopilada a través de encuestas y entrevistas con funcionarios de bibliotecas y descubrí que las percepciones y el comportamiento proyectado varían de biblioteca a biblioteca. Para investigar más a fondo las variaciones en la voluntad de participar en la respuesta e ilustrar las fuerzas impulsoras detrás de tal comportamiento proyectado, exploré las características relacionadas con el contexto en las que operan los funcionarios de las bibliotecas, así como los factores relacionados con las prácticas gerenciales individuales: específicamente, cómo los gerentes se autodefinen en términos de su papel de servicio público y las percepciones que ellos tienen de sus organizaciones.